Properties of blends of starch, polyethylene and poly(ethylene-co-acrylic acid) copolymer - Jeziórska, R.; Żakowska, Z.; Stolbińska, H.; Ratajska, M.; Zielonka, M. (Polimery, 2022)
sUsing reactive extrusion in a twin-screw extruder the blends of low-density polyethylene (PE-LD) with poly(ethylene-co-acrylic acid) (EAA) copolymer 1:1 and 5-30 weight % of potato starch (oxidized - OP or nonoxidized - P) or corn starch (0 were prepared. The static tensile mechanical properties, hardness and melt flow rate (MFR) of the samples were determined. The course of biodegradation of the samples under the influence of selected, amyloliticly active, bacteria strains, actinomycetes and filamentous fungi. Biodecomposition degree has been estimated on the basis of macroscopic and microscopic observations and FT-IR spectrometry. All the samples supported the growth of microbes, the blends with OP - much higher than those with C. It has been also found that biodecomposition degree increased with the starch content in the blend. The highest degree of biodecomposition was observed when Aspergillus niger, Streptomyces (strain 19) and mixture of bacteria of Bacillus type were used.